RETRACTED: The Influence of Company Size, Profitability, Liquidity, And Leverage On Firm Value In Pharmaceutical Sub-Sector Manufacturing Companies Listed On The Indonesian Stock Exchange For The Period 2012-2015 - Juanita Sulistiani; Elwisam Elwisam; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2024)
This study aims to analyze the effect of company size, profitability, liquidity and leverage on firm value in pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2012-2015. This research was conducted by taking a sample of 7 pharmaceutical companies. Samples were taken from the financial statements for each year during 2012-2015. The method used is Multiple Linear Regression Analysis and data testing is carried out with SPSS (Statistical Product and Service Solution) 23 program. The test results show that the overall percentage of company size, profitability, liquidity and leverage on firm value is 74.6% while the rest is explained by other variables not included in this study. The results showed that company size has a positive and significant effect on firm value, profitability has a negative and weakly significant effect on firm value, liquidity has a negative and significant effect on firm value, leverage has a negative and significant effect on Company Value. Suggestions that can be given are that future research by adding a longer time span and using a larger and wider sample to obtain consistency in research results.